Features of Linguistic Terminology in the Field of Agriculture (Wire Insights: Journal of Innovation Insights, 2023)
The article shows the features of the linguistic terminology based on the correspondence materials of the study of the linguo-typological data in foreign languages, the terminological indicator in the agricultural field. The results can be of interest to specialists in the agricultural field of applied lexicography and can also be used as a source of linguistic terminology for didactic purposes.